Optimizing Turning Parameters for The Turning Operations of Inconel X750 Alloy with Nanofluids Using Direct and Aspect Ratio-based Taguchi Methods - Oke, Sunday Ayoola; Adegoke, Ridwan Majekodunmi (Universitas Atma Jaya Yogyakarta, 2021)
For the turning process, the computation of optimal parametric settings for parameters has been traditionally achieved using standard parametric values, but comparative values between the standard parameters have been ignored. But these aspect ratios reveal some evaluation dimensions that account for robust measurement schemes that promote enhanced effectiveness of the process. To address the issue, an aspect-ratio-based mechanism has been introduced to optimize the turning parameters in three Taguchi methodical variants of classical Taguchi, Taguchi-Pareto, and Taguchi-ABC methods. A total of twelve alternatives were developed, with each alternative containing three standard parameters and two aspect ratios since only three standard parameters are involved in the evaluation. The evaluation of parameters in non-prioritized and prioritized forms was considered for each alternative. The Taguchi method accounts for the non-prioritized method, while Taguchi-Pareto and Taguchi-ABC methods are the prioritized parametric structures. The delta values and ranks across the prioritized and non-prioritized parameters were evaluated by their mean values. The optimal parametric settings were evaluated for all alternatives in the prioritized and non-prioritized forms of evaluation. The results, using literature data, confirmed the feasibility of using the approach. The outcome of the methods is in enhancing the planning scheme for the turning operation. The benefit of the study is an enhanced analysis of turning operation’s improvements and estimation of related economic advantages through turning resources conservation.